Формування культури цифрової гігієни - Косенко, М. А.; Пронюк, Г. В. (ХНУРЕ, 2025)
In the modern digital world, cybersecurity is essential for protecting personal information. This article explores common cyber threats such as phishing, malware, password breaches, and DDoS attacks. It highlights key cybersecurity measures, including two-factor authentication, strong passwords, antivirus software, encryption, and regular updates. The importance of digital hygiene practices is also emphasized. Additionally, international cybersecurity regulations, including GDPR, HIPAA, and Ukrainian cybersecurity laws, are discussed.
Keywords: цифрова гігієна; cybersecurity